2020
DOI: 10.3390/nu12123774
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low-Fat and Low-Carbohydrate Diets on Weight Loss and Lipid Levels: A Systematic Review and Meta-Analysis

Abstract: Background: The rise in obesity has emphasised a focus on lifestyle and dietary habits. We aimed to address the debate between low-carbohydrate and low-fat diets and compare their effects on body weight, low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), total cholesterol, and triglycerides in an adult population. Method: Medline and Web of Science were searched for randomised controlled trials (RCTs) comparing low-fat and low-carbohydrate diets up to September 2019. Three i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 75 publications
(39 reference statements)
7
76
1
1
Order By: Relevance
“…Despite these data on LCDs seem promising, meta‐analyses directly comparing several dietary interventions in NAFLD are still lacking. Also, improvements of BMI, HDL‐cholesterol and triglyceride profiles must be balanced with potential consequences of raised LDL‐ and total‐cholesterol levels in the long‐term 59,60 . On a long‐term perspective, carbohydrate intake and overall mortality might still follow a U‐shaped curve 61 …”
Section: Types Of Dietmentioning
confidence: 99%
“…Despite these data on LCDs seem promising, meta‐analyses directly comparing several dietary interventions in NAFLD are still lacking. Also, improvements of BMI, HDL‐cholesterol and triglyceride profiles must be balanced with potential consequences of raised LDL‐ and total‐cholesterol levels in the long‐term 59,60 . On a long‐term perspective, carbohydrate intake and overall mortality might still follow a U‐shaped curve 61 …”
Section: Types Of Dietmentioning
confidence: 99%
“…4 The most recent meta-analysis defined low-carb diets as <40% of energy from carbohydrates and low-fat diets as <30% of energy from fats. 3 Despite differences in how carbohydrate restriction is defined, recent studies suggest that low-carb diets confer more beneficial effects on short-term weight loss and lipid profiles such as triglycerides and high-density lipoprotein (HDL)-cholesterol compared to low-fat diets while having no significant effects on blood pressure or fasting blood glucose. In a recent meta-analysis of 38 RCTs that lasted 6-12 months, participants on low-carb diets (<40% of energy from carbohydrates) exhibited decreased body weight and triglycerides and increased HDL-cholesterol compared to participants on low-fat diets.…”
Section: Factorsmentioning
confidence: 99%
“…Meta-analyses of randomized controlled trials (RCTs) revealed that low-carb diets are at least as effective as low-fat diets in terms of weight loss, but their cardiovascular effects vary in diverse populations. [3][4][5][6] Academic discussions regarding the effects of low-carb diets on short-term weight loss and health outcomes were already rife when television programs promoting low-carb, high-fat diets aired in Korea in 2016 and received huge public attention, triggering the low-carb diet trend in Korea. As a result, many people throughout Korea eat butter and pork belly without hesitation, believing that fat and protein can be consumed in unlimited quantities as long as carbohydrate consumption is restricted.…”
Section: Introductionmentioning
confidence: 99%
“…Meckling et al observed the same outcome [63] The results are largely in line with the recommendations that were published by the Joint Guidelines from the AHA, ACC, and the Obesity Society [64], which stress the importance of following healthy eating patterns, which could be DASH (Dietary Approaches to Stop Hypertension) diet or the Healthy Mediterranean-Style Eating Pattern, instead of simply identifying that one diet is superior to the others. However, studies assessing LFD and LCD are still performed, and Chawla et al recently proved, in their meta-analysis, that LFD had a lesser effect on weight loss when compared to LCD [65]. Table 1 summarizes the trials focusing on LFD in obesity.…”
Section: Low-fat Diet and Obesitymentioning
confidence: 99%